Development of a nutritional screening and assessment indicator system for patients with esophageal cancer in China: Findings from the Delphi method - Jingjing Shang; Wen Dong; Peipei Huang; Yidan Sun; Yuxin He; Hui Li; Shengwu Liao; Mei Li (Cancer Medicine, 2023)
Abstract Background In China, individuals diagnosed with esophageal cancer are confronted with an elevated risk of nutritional inadequacy or malnutrition throughout the course of their disease, a condition that contributes to various adverse clinical outcomes. A vast corpus of data are burgeoning at an unprecedented rate, primarily due to the revolutionary growth of digitalization technologies and artificial intelligence, notably within the domains of health care and medicine. The purpose of this investigation is to initiate the development of a nutritional screening and assessment indicator framework for patients with esophageal cancer within the Chinese context. We seek to furnish an instrumental reference to facilitate preparations for the forthcoming era of advanced, “deep,” evidence‐based medicine. Methods An integrative methodology was employed to forge the preliminary draft of the nutritional screening and assessment indicator system for preoperative patients with esophageal cancer. This encompassed a rigorous literature survey, in‐depth clinical practice investigation, and the facilitation of expert panel discussions. Thereafter, two iterative consultation phases were conducted using the Delphi method in China. The analytic hierarchy process was deployed to ascertain the weighting of each index within the definitive evaluation indicator system. Results The effective response rates for the dual rounds of expert consultation were 91.7% and 86.4%, with commensurate authority coefficients of 0.97 and 0.91. The Kendall harmony coefficients were ascertained to be 0.19 and 0.14 (p < 0.01), respectively. The culminating nutritional screening and assessment indicator system for patients with esophageal cancer comprised 5 primary‐level indicators and 38 secondary‐level indicators. Conclusions The nutritional screening and assessment indicator system contrived for patients with esophageal cancer is underpinned by cogent theoretical principles, leverages an astute research methodology, and manifests dependable outcomes. This system may be appositely utilized as a meaningful reference for the nutritional screening and assessment process in patients afflicted with esophageal cancer.